Neurocognitive functioning in symptomatic adults with sickle cell disease: A description and comparison with unaffected siblings. Issue 9 (20th October 2020) - Martin, Staci; Roderick, Marie Claire; Abel, Cristina; Wolters, Pamela; Toledo-Tamula, Mary Anne; Fitzhugh, Courtney; Hsieh, Matthew; Tisdale, John
ABSTRACT: Children and adults with sickle cell disease (SCD) are at risk for neuropsychological deficits; however, the neurocognitive functioning of adults with SCD and related comorbidities has not been widely reported in the literature. We examined specific cognitive domains in symptomatic adults with SCD and compared them with their unaffected siblings. We also examined relationships between cognitive scores, patient-reported outcomes (PROs), and medical/laboratory values. Thirty patient-sibling pairs ( M patient age = 32.5 years, M sibling age = 32.1 years) completed evaluations as part of a medical clinical trial (NCT00061568). All patient and sibling neurocognitive test scores were within normal limits. Patients scored significantly lower ( M  = 91.0 ± 11.3) than their siblings ( M  = 100.6 ± 12.3; t  = −3.5, p  < .01) on the Wechsler Processing Speed Index. They also indicated more problems than siblings on an executive functioning questionnaire, although these differences were nonsignificant after accounting for depressive symptoms. Higher fetal hemoglobin and lower creatinine correlated with better scores on particular cognitive and PRO measures. In summary, our sample of adults with symptomatic SCD demonstrated worse processing speed and experience more executive challenges than their siblings, despite treatment with hydroxyurea. These relative weakness likely relate to disease processes but the specific physiological mechanism is unclear.